Making global and local connections : historical perspectives on ports - Bergholm, Tapio, 1958-; Fischer, Lewis R.; Tonizzi, M. Elisabetta (Research in maritime history, 2007)
This book provides a series of case studies concerning ports and port communities from around the world, in attempt to determine the impact of globalisation on the port industry and the link between local and global port conditions.